Pelatihan Pemetaan Spasial Bencana Alam bagi Guru dan Siswa SMA di Wilayah Kepulauan - Lasaiba, Mohammad Amin; Sihasale, Daniel Anthoni; Osok, Rafael Marthinus (Jurnal Pengabdian Arumbai, 2025)
Spatial mapping training for teachers and students in island regions was conducted to strengthen schools’ capacity to understand environmental risks through geospatial technology utilization. This activity was motivated by limited data access and low spatial literacy in coastal schools vulnerable to disasters. It aimed to enhance teachers’ and students’ skills in identifying, mapping, and analyzing potential hazards around school environments. The participatory and collaborative approach involved training sessions, field practices, and digital mentoring using open-source software. The results showed significant improvements in spatial literacy, risk analysis ability, and school autonomy in developing local risk maps. The community-based spatial training model strengthened school disaster preparedness and fostered an inter-school collaborative network. This approach provides scientific contribution to applied disaster education. Its implication encourages local governments and educational institutions to replicate similar programs sustainably.